NSAID-INDUCED GASTROINTESTINAL ULCER DISEASE: MECHANISM, PREVALENCE, AND PREVENTION (International journal of medical sciences, 2025)
Nonsteroidal anti-inflammatory drugs (NSAIDs) represent one of the most widely prescribed and over-the-counter drug categories worldwide. They are integral to the management of pain, inflammation, and fever in medical specialties such as rheumatology, orthopedics, neurology, and general practice. Despite their clinical utility, prolonged or inappropriate use of NSAIDs is associated with a spectrum of gastrointestinal (GI) toxicities, ranging from mild gastritis to severe peptic ulcer disease and life-threatening bleeding or perforation. This paper explores the mechanisms, epidemiological burden, and prevention of NSAID-induced gastrointestinal ulcer disease.